Plaster Stemming Application at a Basalt Quarry: a Case Study - Cevizci, Halim; Yavuz, Hüseyin; Caran, Şemsettin; Tosun, Yıldırım İsmail (TMMOB MADEN MUHENDISLERI ODASI, 2015)
In this study, plaster stemming application at a basalt quarry was investigated. For comparison of two stemming method, test blasts were carried out in the same quarry bench. For unit volume rock, plaster stemming provided lower cost than drill cuttings stemming. Because, burden and spacing distances were increased at plaster stemming round. Although length of charge column was increased, the cost of unit volume rock was lower for plaster stemming round. Rock piles fragmentation of plaster stemming round and drill cuttings stemming round were similar.
Keywords: Plaster stemming; blasting; Stemming; Fragmentation; Vibration